Empire Lost: France and its other worlds - Mudimbe-Boyi, Elisabeth (Lexington Books, 2009)
Despite the loss of the French Empire, France and its former colonies are still bound by a common historical past. With the new global promotion of la Francophonie, the relation between the various constituencies of the French-speaking regions of the world is reexamined and debated in this book, through the conversation between scholars dealing with diverse texts and contexts that present the colonial contact and its imprint. The book illustrates how, in France and in its other worlds, that contact, its repercussions, and its memory are lived and expressed today in a variety of textual representations. The historical contact between France and its other worlds has given birth to new kinds of cross-cultural expressions in the arts, in literature, and in aesthetics, establishing interrelations and generating appropriations from both sides of the Hexagon frontier, highlighting the fluidity and the permeability of its cultural borders. The book subtext tells that the frontier between France and its other worlds is no more an unshakable geographical, political, and cultural limit, but rather a line that has become mobile, fluctuating, and permeable, and across which currents, ideas, sensitivities, and creativity are expressed, bearing testimony to vitality and diversity but also to a cross-fertilization of cultures and societies (re) crossing or meeting at that line. Seen from this latter perspective, the book comes also as an interrogation of the inclusiveness or exclusiveness of the words francophone and Francophonie, and, at an academic level, a mutual exclusion of French and Francophone Studies.